Comparative Pharmacokinetics and Bioequivalence of Pour-On Ivermectin Formulations in Korean Hanwoo Cattle - Suyoung Kim; HyunYoung Chae; Eon-Bee Lee; Gayeong Lee; Seung-Chun Park; Jeongwoo Kang (MDPI AG, 2023)
This study aimed to conduct a bioequivalence study of applying three pour-on ivermectin formulations at a dose of 1 mg/kg on the back of Korean native beef cattle (Hanwoo). To conduct bioequivalence testing, the pharmacokinetics of three groups (control Innovator, test Generic A, and test Generic B) of five clinically healthy Korean Hanwoo cattle (average weight 500 kg) were studied. After topical application to the skin, blood samples were drawn at the indicated times. These blood samples were analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). The time required to reach the maximum concentration (Tmax), the maximum concentration (Cmax), and the area under the curve (AUClast) of each pharmacokinetic parameter were compared for bioequivalence. The results showed that the control had a Tmax of 41 ± 1.24 h, a Cmax of 0.11 ± 0.01 μg/mL, and an AUClast of 9.33 ± 0 h*μg/mL). The comparator Generic A had a Tmax of 40 ± 1.14 h, a Cmax of 0.10 ± 0.01 (μg/mL, and an AUClast of 9.41 ± 0.57 h*μg/mL, while Generic B had a Tmax of 40 ± 2.21 h, a Cmax of 0.10 ± 0.01 μg/mL, and an AUClast of 9 h*μg/mL. The values of the bioequivalence indicators Cmax, Tmax, and AUC were all within the range of 80% to 120%, confirming that all three tested formulations were bioequivalent. In conclusion, the study showed that the two generic products were bioequivalent to the original product in Hanwoo cattle.